Comparative Study on Frying Performance of Three Different Oils for the Preparation of Ripe Plantain Banana - Pambou-tobi, N. P. G.; Sompila, Arnaud W. G. Tamba; Niamayoua, Rosalie Kama; Linder, Michel (European Journal of Applied Sciences, 2022)
In this study, the effect of traditional frying on oils degradation namely frial oil (FO), soybean oil (SBO) and refined blanded deodorized palm olein oil (RBDPOo) was investigated. Oils degradation was monitored by measuring the free fatty acids (FFA), peroxides (PV), p-anisidine (p-AV),) iodine value (IV), totox value (TxV), total polar compounds (TPC), fatty acid composition and C18:2/C16:0 ratio, viscosity, conjugated dienes (CD) value and oil color. Oils samples were taken every 4 h of frying during 10 consecutive days. Values of all physic-chemicals measures significantly changed with frying and type of fat. Values of FFA, p-AV, TPC, CD, TxV, ΔE and viscosity increased significantly, whereas IV and C18:2/C16:0 ratio decreased significantly at the end of the frying processes. Excepted PV, where the values reached a maximum and then decreased at to final frying. These results suggested that a traditional frying process has an impact on degradation on edible oils.